2013
DOI: 10.3109/15368378.2013.773910
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species (ROS) production in human peripheral blood neutrophils exposedin vitroto static magnetic field

Abstract: The aim of this study was to determine the effect of gradient static magnetic field (SMF) on reactive oxygen species (ROS) production in human neutrophils in peripheral blood in vitro. Blood samples collected from healthy individuals were incubated in an inhomogeneous SMF (in a south or north pole of the field) for 15, 30 or 45 minutes. The maximum value of induction (B max) amounted to ≈ 60 mT. To determine the strength of the ROS production, dihydrorhodamine (123DHR) as fluorophore and phorbol 12-myristate 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Goraca and colleagues [ 22 ] reported a decrease in antioxidant capacity in hearts of rats subjected to chronic LF-EMF exposure. Similarly, prolonged exposure to LF-EMF enhanced free radical generation in the brain and retina of rats leading to the reduced antioxidant defense capacity and increased lipid peroxidation [ 23 25 ]. Recently, it has been shown that the exposure of blood samples to LF-EMF induced changes in ROS production in both stimulated and nonstimulated neutrophils [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Goraca and colleagues [ 22 ] reported a decrease in antioxidant capacity in hearts of rats subjected to chronic LF-EMF exposure. Similarly, prolonged exposure to LF-EMF enhanced free radical generation in the brain and retina of rats leading to the reduced antioxidant defense capacity and increased lipid peroxidation [ 23 25 ]. Recently, it has been shown that the exposure of blood samples to LF-EMF induced changes in ROS production in both stimulated and nonstimulated neutrophils [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Poniedzialek et al also showed that in human peripheral blood neutrophils, ROS level was significantly reduced after 60 mT SMF exposed for 15 min, but recovered to control level at 30 min. More surprisingly, ROS level was later visibly elevated at 45 min, but only in the cells that were exposed to the south poles of the magnets, not north poles [ 30 ], indicating that the effects of SMFs on cellular ROS were dependent on both exposure time and the magnetic poles. It could be argued that these effects are likely due to MF direction, rather than the magnetic poles themselves.…”
Section: The Effects Of Magnetic Fields On Rosmentioning
confidence: 99%
“…Furthermore, in a recent study a significant decline in ROS production by human peripheral blood neutrophils has been shown after 15 min exposure to SMF (approx. 60 mT), while a longer incubation time (45 min) caused a reverse phenomenon [41]. The authors conclude that the SMF-exposure may directly modulate the activity of neutrophil NADPH oxidases and they highlight the importance of proper adjustment of exposure time to SMF for any potential therapeutic applications.…”
Section: Discussionmentioning
confidence: 89%